Engines of change : a history of the American dream in fifteen cars - Ingrassia, Paul (Simon & Schuster, 2012)
Chronicles the history reflected by fifteen iconic car models to discuss how automobiles reflect key cultural shifts as well as developments in such areas as manufacturing, women's rights, and environmental awareness.